A new species of Amyema (Loranthaceae) and a new Gastrodia (Orchidaceae) record for the Philippines from Negros Island - Pelser, Pieter B.; Olimpos, Shiella Mae B.; O’byrne, Peter; Barcelona, Julie F. (Phytotaxa, 2018)
Our recent fieldwork in the island of Negros, Philippines resulted in the discovery of a species new to science, Amyema lisae (Loranthaceae), and a new record for the Philippines, Gastrodia sabahensis (Orchidaceae), which we describe and report here. Amyema lisae differs from similar species with verticillate phyllotaxy and inflorescences of simple umbels by having relatively smaller leaves and 5-merous flowers that are yellow and tomentose. This new species is named in honor of Lisa J. Paguntalan, a champion of biodiversity conservation in the Philippines. In the same island, we also collected Gastrodia sabahensis, previously only known to occur in Borneo. Our specimens differ from typical plants of this species by having larger flowers with column bases that are slightly broader and stelidia that are broad with blunt apices.